2019
DOI: 10.1111/joa.13137
|View full text |Cite
|
Sign up to set email alerts
|

Elevated activity levels do not influence extrinsic fiber attachment morphology on the surface of muscle‐attachment sites

Abstract: Extrinsic fibers (EFs) are a type of penetrating collagenous fiber, closely related to the periodontal ligament, which help anchor soft tissue into bone. These fibers are associated with muscle attachment sites (entheses). Their size and grouping patterns are thought to be indicative of the loading history of the muscle. EFs are of particular significance in anthropology as potential tools for the reconstruction of behavior from skeletal remains and, specifically, entheses. In this study, we used a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…Interestingly, both Zumwalt (2006) and Rabey et al (2015) observed a positive effect of exercise on bone formation rate, suggesting that a bone's internal microstructure may be more informative than macroscopic surface observations. However, analysis of the distribution and morphology of extrinsic fibers, the collagenous fibers directly anchoring muscle into the bone, demonstrated no clear variation between experimental activity groups in mice also used in the present study (Turcotte et al, 2020).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Interestingly, both Zumwalt (2006) and Rabey et al (2015) observed a positive effect of exercise on bone formation rate, suggesting that a bone's internal microstructure may be more informative than macroscopic surface observations. However, analysis of the distribution and morphology of extrinsic fibers, the collagenous fibers directly anchoring muscle into the bone, demonstrated no clear variation between experimental activity groups in mice also used in the present study (Turcotte et al, 2020).…”
Section: Introductionmentioning
confidence: 53%
“…When considering internal structure, Djukic et al (2015) found no link between trabecular or cortical bone architecture and surface morphology at enthesis sites of the lower limb in human archaeological samples. But this would be expected if surface morphology is not responsive, in a straightforward manner, to the local strain environment of the individual enthesis as the experimental studies suggest (Rabey et al, 2015;Turcotte et al, 2020;Wallace et al, 2017;Zumwalt, 2006).…”
Section: Characterizing Enthesis Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of muscle attachment sites has been widely used to estimate muscle size and function in archeological populations, even serving as a basis from which to infer occupational intensity (Karakostis et al, 2017) or the practice of specific activities such as harpoon launching (Hawkey & Merbs, 1995). However, neither direct measurements of attachment size (e.g., see Hawkey & Merbs, 1995;Henderson, 2013;Henderson et al, 2013;Milella, 2014) nor calculations of optical complexity (Wallace et al, 2017;Zumwalt, 2006) are supported consistently by experimental studies (see Rabey et al, 2015;Turcotte et al, 2020;Wallace et al, 2017;Williams-Hatala et al, 2016;Zumwalt, 2006). For example, Rabey et al (2015) demonstrated a clear division in the mass and internal architecture of the F I G U R E 4 Phylogenetic generalized least squared (PGLS) regressions of residuals of bony proxies against masseter mass (left) and masseter PCSA (right), following adjustment for body mass.…”
Section: Evaluating Bony Predictors Of Muscle Sizementioning
confidence: 99%
“…Moreover, muscle attachment areas have been shown to be of varying value for predicting muscle size and strength within other skeletal regions. While correlations between muscle size/force and entheseal areas have been questioned in several postcranial regions (e.g., Turcotte et al, 2020; Wallace et al, 2017; Zumwalt, 2006), some morphometric approaches have suggested a relationship between muscle force potential (i.e., PCSA) and external bony morphology (Harbers, Neaux, et al, 2020; Harbers, Zanolli, et al, 2020). Thus, the predictive value of muscle attachment sites for the estimation of myological properties remains contentious.…”
Section: Introductionmentioning
confidence: 99%